Coupling Analysis of Low-Speed Multiphase Flow and High-Frequency Electromagnetic Field in a Complex Pipeline Structure. (12th January 2014) - Huo, Xiaokai; Sun, Weitao; He, Fengjiang; Yang, Zhe; Peng, Yuanping
Abstract : Accurate estimation of water content in an oil-water mixture is a key technology in oil exploration and production. Based on the principles of the microwave transmission line (MTL), the logging probe is an important water content measuring apparatus. However, the effects of mixed fluid flow on the measurement of electromagnetic field parameters are rarely considered. This study presents the coupling model for low-speed multiphase flow and high-frequency electromagnetic field in a complex pipeline structure. We derived the S -parameter equations for the stratified oil/water flow model. The corresponding relationship between the S -parameters and water holdup is established. Evident coupling effects of the fluid flow and the electromagnetic field are confirmed by comparing the calculated S -parameters for both stratified and homogeneous flow patterns. In addition, a multiple-solution problem is analyzed for the inversion of dielectric constant from the S -parameters. The most sensitive phase angle range is determined to improve the detection of variation in the dielectric constant. Suggestions are proposed based on the influence of the oil/water layer on measurement sensitivity to optimize the geometric parameters of a device structure. The method proposed elucidates how accuracy and sensitivity can be improved in water holdup measurements under high water content conditions.